Hubungan Kebiasaan Membaca Karya Sastra dan Keterampilan Menulis Puisi - Putri, Widya Amalia; Mulyaningsih, Indrya; Itaristanti (Kajian Bahasa dan Sastra (KABASTRA), 2023)
This study aims to describe: (1) the habit of reading literature, (2) the skill of writing poetry, (3) the relationship between the habit of reading literature and the skill of writing poetry in class IX students of SMPN 3 Losari Brebes. This research is a qualitative correlation research. Data were analyzed using descriptive statistical techniques, the results of this study are as follows. First, based on the results of data analysis on the habit of reading literary works, it can be obtained that 4 students (12%) are in the very good category, 12 students (36%) are in the high category, 14 students (43%) are in the low category and 3 are in the very good category. students (9%) in the very low category. The reading habit of class IX students of SMPN 3 Losari Brebes can be said to be moderate. Second, based on the analysis of poetry writing skill data, information can be obtained that there are 8 students (24%) in the very high category, 7 students (21%) in the high category, 15 students (46%) in the low category and 3 students ( 9%) in the very low category. The skill of writing poetry for class IX students of SMPN 3 Losari Brebes can be said to be moderate. Third, there is a positive and significant relationship between reading habits and poetry writing skills in SMPN 3 Losari Brebes students. Pearson Correlation value of 0.918 (perfect category). The implication of the results of this study is that poetry writing skills are determined by several factors, one of which is the habit of reading literary works. To improve students' poetry reading skills, it is necessary to make efforts to increase the habit of reading literature which has a positive and significant relationship between the habit of reading literary works and the skill of writing.